Scientific justification of spatial distribution and mapping of anomalous manifestations of white hydrogen – energy raw material of the XXI century - I. D. Bahrii; О. О. Riepkin; S. O. Paiuk; Ia. M. Kryl (Мінеральні ресурси України, 2023)
The research studied the pressing problem of the fuel and energy strategy of the XXI century. For the first time, there was shown the diversity of the authors approach to theoretical and applied problems of hydrogen energy.